Perancangan E-Commerce Berbasis Web Pada Toko Tas Brandes Leather Menggunakan Metode Prototype - I Kadek Adi Sanjaya Putra Sanjaya; Putri Anugrah Cahya Dewi (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2021)
Utilization of the web today can also be used for trading activities such as E-Commerce. E-Commerce is used by traders to facilitate the sale of a product and process transactions. During this pandemic, E-Commerce is very necessary. During this pandemic, people were more interested in shopping online, according to the latest annual report from the solution-commerce startup, Sirclo, entitled "Navigating Indonesia E-Commerce COVID-19 Impact & The Rise of Social Commerce" showing that 12 million new E-Commerce users during the COVID-19 pandemic. This is because the majority of customers are afraid to leave their homes because of the pandemic. One of the shops affected was Brandes Leather, which is an offline-based shop. During this pandemic, the turnover obtained by this shop decreased, because tourists were not allowed to visit Bali. This research aims to help shop sellers design a web-based E-Commerce, which later this web-based E-Commerce will be able to be used as a medium for promotion and transactions between buyers and sellers, not only useful for sellers, buyers will also find it easy to shop from home and get information about the product to be purchased through E-Commerce itself. The result of this study is a web-based e-commerce design at a brandes leather bag shop using the prototype method so that later this shop's product enthusiasts can shop from their homes, and can get information about this shop's products easily.